PENGARUH INDEKS SAHAM GLOBAL DAN KONDISI MAKRO INDONESIA TERHADAP INDEKS HARGA SAHAM GABUNGAN BURSA EFEK INDONESIA - Pardomuan Sihombing,; Rizal , (Media Ekonomi, 2014)
The objective of this research is to examine the effect of global stock indices and marco economic condition of Indonesia to Jakarta Stock Exchange Composite Index (JCI). The global stock indices that had been analyzed in this research are Dow Jones Industrial Average (DJIA), Nikkei 225 (N225), Shanghai Stock Exchange Composite (SSE), Financial Times Stock Exchange 100 (FTSE 100), and Hang Seng Index (HSI). The macro economic indicator that had been analyzed in this research are exchange rate United States dollar to Indonesian rupiah, inflation and BI rate. This research was conducted using secondary data. Research periods are 10 years for 120 months since January 2008 until December 2012. This study was analyzed by using error correction model (ECM). By using this method, it can be analyzed the short and long term influence from the independent variables to the dependent variable with its analysis techniques to correct long term imbalances. The result shows that in short term, only DJIA, exchange rate and BI rate have significant effect on JCI. While in long term, DJIA, N225, SSE, HSI, and BI rate have significant effect on JCI. Adjusted R-square value of 0.444987 can illustrate that the dependent variable is explained by the independent variables for 44.499 percent, while the rest are influenced by the other variables.